Balance of Power Dalam Intervensi Arab Saudi Pada Konflik Yaman yang Terjadi Pasca Arab Spring - Farras, Ahmad Naufal; Pattipeilohy, Shary Charlotte Henriette (Journal of International Relations, 2020)
The internal Yemen conflict post Arab Spring is one of the conflicts in the Middle East affected by the Arab Spring incident. The demonstration was carried out until Ali Abdullah Saleh was officially stepped down in 2012 and replaced by Abdrabbuh Mansour Hadi. However, in 2014 another conflict arose when Houthis was launched millitary attacks and successfully seized control of the Yemeni capital, Sana’a. Until finally President Hadi fled to Saudi Arabia to ask for international intervention. This research tries to explain the reasons for intervention by Saudi Arabia in the Yemen conflict that occurred after the Arab Spring. In analyzing the case, this study will use the concept of balance of power. According to Ziegler, the balance of power operates with four principles; being suspicious of an increase of the power by another country, always ally with the weaker side, support a state only until it is out of danger, and show moderation toward the aggressor after it is defeated. In addition to fulfilling President Hadi’s desires the results of this study indicate that the intervention carried out by Saudi Arabia in the Yemen conflict was also as an effort for balancing the power to restrain Iran's movement for spreading its influence in the Middle East